From silos to systems: Reimagining zoonotic neglected tropical disease management through the lens of one health - Adiwinoto, Ronald Pratama; Adnyana, I Made Dwi Mertha; Soedarsono, Soedarsono; Gustam, Tasalina Yohana Parameswari (Svāsthya: Trends in General Medicine and Public Health, 2024)
Zoonotic neglected tropical diseases (zNTDs) pose significant global public health challenges, particularly in low-income and middle-income countries. Traditional siloed approaches to zNTD management have proven inadequate for addressing the complex interplay between human, animal, and environmental health factors. This review examined the limitations of fragmented strategies and explored the potential of integrated one-health approaches for more effective zNTD control. This narrative review covered publications from 2000 to 2023, sourced from databases including PubMed and Scopus, emphasizing studies that met inclusion criteria of peer-reviewed research focused on zNTDs through a One Health lens. A comprehensive analysis of the current literature and case studies was conducted to evaluate the multifaceted drivers of zoonotic pathogen spillover, assess the economic and health impacts of zNTDs, and identify successful implementation of the One Health strategy in endemic regions. This review highlights the inadequacies of siloed disease management approaches, which often lead to inefficient resource allocation and missed opportunities for synergistic intervention. Successful case studies have demonstrated the effectiveness of the One Health strategy in improving disease surveillance, enhancing cross-sectoral collaboration, and achieving sustainable health outcomes. The potential of emerging technologies and innovations to support integrated approaches has also been explored. Transitioning from siloed to systemic approaches in zNTD management requires overcoming institutional barriers, fostering cross-sector collaboration, and implementing multitiered frameworks that operate at the local, national, and global levels. Investing in cross-sectoral capacity development and leveraging technological innovations are crucial for building a workforce capable of addressing the complex challenges posed by zNTDs. Adopting the One Health principle offers a promising path toward more comprehensive, efficient, and sustainable strategies for zNTD prevention.